Analysis of Interactive Learning Media Needs for Computer Network Installation in Grade X SMK - Nurcahyo, Ratih Widya; Koriaty, Sri (Juwara: Jurnal Wawasan dan Aksara, 2025)
This study analyzes students perceptions of using interactive multimedia in Computer Network Installation learning. A quantitative descriptive method was employed, using questionnaires completed by 40 students enrolled in the course. Results indicate that most students support the use of interactive multimedia, mainly because it displays engaging objects (25.0%) and facilitates learning (17.5%). Additionally, 12.5% found the media attractive and appreciated that it does not require internet access. Smaller percentages noted benefits such as talent development and keeping up with technology (7.5% each). However, challenges were also identified, with 70.0% of students reporting difficulties in understanding how to use the media and 25.0% citing limitations due to their phone specifications. Only 5.0% reported no challenges. Overall, interactive multimedia received positive feedback, particularly for enhancing material visualization and easing learning. To address challenges, it is recommended to provide clear training on media use before implementation and to design multimedia compatible with students devices.